A Case of Spontaneous Spinal Subdural Hematoma Complicated by Cranial Subarachnoid Hemorrhage and Spinal Adhesive Arachnoiditis - Taihei Go; Toshiyuki Tsutsui; Yasuaki Iida; Katsunori Fukutake; Ryoichi Fukano; Kosei Ishigaki; Kazuaki Tsuchiya; Hiroshi Takahashi (Case Reports in Orthopedics)
A 76-year-old woman with a spinal subdural hematoma (SDH) was presented with severe back pain without headache. Magnetic resonance imaging (MRI) performed 4 days after onset showed SDH extending from Th2 to L3. She was diagnosed with spontaneous SDH without neurological manifestation, and conservative treatment was selected. Transient disturbance of orientation appeared 7 days after onset. Small subarachnoid hemorrhage (SAH) was detected on head CT, and strict antihypertensive therapy was started. Symptoms changed for the better. Back pain disappeared 4 weeks after onset. On follow-up MRI at 6 months after onset, the SDH had been resolved spontaneously. Although adhesive arachnoiditis was observed at Th4-6, the recurrence of clinical symptoms was not observed at one year and a half after onset. Spinal subdural space is almost avascular; a hematoma in a subdural space is considered to come from a subarachnoid space when it is a lot. A hemorrhage in subarachnoid space was flushed by cerebral spinal fluid; hematoma or arachnoiditis was not formed in general. In our case, hemorrhage was a lot and expansion of SDH was large enough to cause cranial SAH and arachnoiditis. But longitudinally expanded SDH did not show neurological manifestation and resolved spontaneously in our case.